Investigation of flow dynamics and governing mechanism of choked flow for cavitating jet in a poppet valve. (February 2019) - Yuan, Cong; Song, Jinchun; Liu, Minghe
Highlights: A numerical method is developed for cavitating flow, which considers compressibility of both liquid and vapor phases. Development of cavitation in poppet valve is investigated both numerically and experimentally. Jet dynamics is discussed in details according to its gradual development. Governing mechanism for choked flow is investigated. Abstract: Poppet valve is widely used in oil hydraulics due to its simple and robust structure. With occurrence of cavitation, serious choking is possibly triggered in a poppet valve and its governing mechanism is yet unknown. In order to investigate cavitating jet, a compressible, two-phase method for cavitating flow is developed based on OpenFOAM, which (1) incorporates VOF phase-fraction interface capturing technique in an Eulerian framework; (2) involves special treatment for transonic case; (3) allows separate exhibition and analysis of examination of diverse influences on the fragmentation process of potential core; (4) is expected in due course to provide a detailed picture of the mechanisms that govern the choking formation. The numerical approach is combined with experiment to perform a systematic investigation of the choking phenomenon. Calculation results are shown to be generally consistent with experiment in terms of flow performance and cavity structure. Therefrom the following analysis and discussion are performed. (1) The choked flow is investigated based on development in cavitation structure with respect to pressure drop. (2) The computational and experimental results are combined to provide a comprehensive evolution process of the jet with increase in pressure drop. It clarifies that the cavitation inception is close associated with transition in flow pattern. (3) The jet dynamics is divided into several stages according to gradual development, which is in detailed discussed separately. (4) Results also confirm the periodic performance of cavitation. The cyclic shedding of bubble cluster is utilized to interpret the disintegration of potential core.